Rapid-response radio observations of short GRB 181123B with the Australia Telescope Compact Array - Anderson, Gemma; Bell, M.E.; Stevens, J.; Aksulu, M.D.; Miller-Jones, James; Horst, AJ van der; Wijers, R.A.M.J.; Rowlinson, A.; Bahramian, Arash; Hancock, Paul; Macquart, Jean-Pierre; Ryder, S.D.; et al. (Oxford University Press, 2021)
We introduce the Australia Telescope Compact Array (ATCA) rapid-response mode by presenting the first successful trigger on the short-duration gamma-ray burst (GRB) 181123B. Early-time radio observations of short GRBs may provide vital insights into the radio afterglow properties of Advanced LIGO- and Virgo-detected gravitational wave events, which will in turn inform follow-up strategies to search for counterparts within their large positional uncertainties. The ATCA was on target within 12.6 hr post-burst, when the source had risen above the horizon. While no radio afterglow was detected during the 8.3 hr observation, we obtained force-fitted flux densities of $7 ± 12$ and $15 ± 11~μ$Jy at 5.5 and 9 GHz, respectively. Afterglow modelling of GRB 181123B showed that the addition of the ATCA force-fitted radio flux densities to the Swift X-ray Telescope detections provided more stringent constraints on the fraction of thermal energy in the electrons (log$ε_e = -0.75^{+0.39}_{-0.40}$ rather than log$ε_e = -1.13^{+0.82}_{-1.2}$ derived without the inclusion of the ATCA values), which is consistent with the range of typical $ε_e$ derived from GRB afterglow modelling. This allowed us to predict that the forward shock may have peaked in the radio band $\sim10$ days post-burst, producing detectable radio emission $\gtrsim3-4$ days post-burst. Overall, we demonstrate the potential for extremely rapid radio follow-up of transients and the importance of triggered radio observations for constraining GRB blast wave properties, regardless of whether there is a detection, via the inclusion of force-fitted radio flux densities in afterglow modelling efforts.